Accuracy Analysis Of News Content About Islam On Online Media Radar Bogor (International Journal of Education and Literature, 2022)
Online media news is known for its lack of credibility in conveying information and its lack of prioritizing objectivity (accuracy, fairness , completeness) in pursuit of instantaneousness. There is quite a bit of news that puts Muslims in a corner, creating a negative image of the Islamic religion . This research aims to find out how the Radar Bogor media presents news content, as well as knowing the accuracy of news content about Islam on the Radar Bogor online media. This research uses the library research method or library study using Roland Barthes' Semiotics. The assessment categories in analyzing accuracy are in accordance with research conducted by the Press Council in reporting research on 28 newspapers in Java in 2004, including checking, writing errors, relevant news sources, title and content accuracy, photo and content accuracy. The results of the research show that in terms of checking and rechecking, suitability of photos and news content, relevant news sources, suitability of news titles and content, Radar Bogor accurately presents news about Islam. However, in news writing, the 5W 1 H element is complete, the sentences are connected to each other. In spelling, typos or typos were found in 6 news stories which did not reduce the original meaning.